Health-related quality of life in children after surgical treatment of non-syndromal craniosynostosis - Shavlokhova, Veronika; Grüninger, Steffen; Hoffmann, Jürgen; Freudlsperger, Christian; Engel, Michael (Journal of cranio-maxillofacial surgery, 2021)
Purpose - Craniosynostosis is a premature ossification of the fibrous sutures in a skull which results in a changing of the growth pattern of the skull with abnormal head shapes, midface hypoplasia, and neurofunctional disorders. Surgical correction of craniosynostosis by opening the ossified cranial sutures is usually made in the infant phase to avoid compression of the brain and mental deficits. However, little is known regarding the health-related quality of life among children after surgical treatment of diverse forms of craniosynostosis. The purpose of this study was to evaluate the quality of life of adolescent patients who anderwent a surgical correction of non-syndromal craniosynostosis in infancy. - Materials and methods - The study population included 48 adolescents with an average age of 12.1 ± 4.3 years. The KINDL questionnaire, which was specifically validated for children, was used to estimate different dimensions of quality of life and the impact of various factors on it. - Results - In the investigated group, boys were more likely to be affected by non-syndromal craniosynostosis than were girls. Children and their parents showed a high degree of correlation in each of the investigated dimensions of the KINDL questionnaire. Sex, the type of craniosynostosis, surgical technique, and surgical result did not seem to have an influence on the quality of life. A negative correlation between the time of surgery and the family-related quality of life could be shown. None of the patients in the study had relevant limitations or impairments in their later life. - Conclusions - In our study, patients with simple non-syndromic craniosynostoses who anderwent operative correction of craniosynostosis in infancy do not show any quality-of-life limitations in their later life compared to the average population.
Gesehen am 22.08.2021
Publikationsdatum online: 27 April 2019